Thinking Outside the Box: Co-planning Scientific Presentations with Virtual Agents - Trinh, Ha; Edge, Darren; Ring, Lazlo; Bickmore, Timothy (Proceedings of the Sixteenth International Conference on Intelligent Virtual Agents (IVA 2016), 2016)
Oral presentations are central to scientific communication, yet the quality of many scientific presentations is poor. To improve presentation quality, scientists need to invest greater effort in the creative design of presentation content. We present AceTalk, a presentation planning system supported by a virtual assistant. This assistant motivates and collaborates with users in a structured brainstorming process to explore engaging presentation structures and content types. Our study of AceTalk demonstrates the potential of human-agent collaboration to facilitate the design of audience-centered presentations, while highlighting the need for rich modelling of audiences, presenters and talk contexts.